An introduction to farming and biomass utilisation of marine macroalgae. Issue 5 (3rd September 2019) - Buschmann, Alejandro H.; Camus, Carolina
ABSTRACT: The interest in seaweeds by humans seems to have originated over 1700 years ago when several seaweed species became used in ethnic cuisines. These initial applications enabled the start of farming in Japan, China and Korea. However, in Western countries, demand for seaweed polysaccharides began only after World War II, when the demand for agar, alginate and carrageenans developed. At the present time, many researchers and entrepreneurs predict a promising future for innovation in the seaweed industry. In this context, this special issue covers some advances and constraints that seaweed farming and the utilisation of its biomass face today.